Hubungan Kinerja Pustakawan dan Fasilitas Perpustakaan dengan Kepuasan Pelanggan di Perpustakaan Institut Teknologi dan Bisnis Indragiri - Aris Triyono; Desi Amidasti (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
Abstract: This study aims to see the relationship between librarian performance and library facilities with customer satisfaction at the Indragiri Institute of Technology and Business library. This study uses a Cross-sectional Study survey design with a population of Indragiri Institute of Technology and Business students 2024-2025. The technique used in this study is saturated sampling or total sampling of 130 students. The data analysis technique used in this study is simple correlation analysis and multiple regression analysis. The results of the study show that: (1) There is a relationship between librarian performance and customer satisfaction at the Indragiri Institute of Technology and Business library. of 0.721 with a significance value of 0.000 so that the calculated r value ≥ r table or 0.721 ≥ 0.172 can be said to be significant. Because r count ≥ r table then Ho is rejected and Ha is accepted; (2) There is a relationship between library facilities and customer satisfaction of 0.535 with a significance value of 0.000, so that r count ≥ r table or 0.535 ≥ 0.172, it can be said to be significant. Because r count ≥ r table, Ho is rejected and Ha is accepted; (3) There is a relationship between librarian performance and library facilities together with customer satisfaction at the Indragiri Institute of Technology and Business library of 0.769, so it can be concluded that librarian performance and library facilities together have a correlation with customer satisfaction.